2008
DOI: 10.1016/j.jasms.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of phospholipids by ion mobility TOFMS

Abstract: Combining© matrix-assisted© laser© desorption/ionization© (MALDI)© mass© spectrometry© with© ion mobility© (IM)© results© in© the© fast© sorting© of© biomolecules© in© complex© mixtures© along© trend© lines. In© this© two-dimensional© (2D)© analysis© of© biological© families,© lipids,© peptides,© and© nucleotides are© separated© from© each© other© by© differences© in© their© ion© mobility© drift© times© in© a© timescale© of hundreds© of© microseconds.© Molecular© ions© of© similar© chemical© type© fall© along©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 28 publications
12
111
0
Order By: Relevance
“…As a consequence, changing the cation (e.g. from H + to Ag + ) turns out to be an important feature to adjust / improve the separation of isomers [8,9,11]. Mobilograms showing the TIMS analysis of THC (grey trace) and CBD (black trace) as their adduct ions are depicted in Fig.…”
Section: Separation Of Isomers Employing Cation Adduct Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, changing the cation (e.g. from H + to Ag + ) turns out to be an important feature to adjust / improve the separation of isomers [8,9,11]. Mobilograms showing the TIMS analysis of THC (grey trace) and CBD (black trace) as their adduct ions are depicted in Fig.…”
Section: Separation Of Isomers Employing Cation Adduct Formationmentioning
confidence: 99%
“…A common approach to separate isomers, which exhibit similar collision cross section (CCS (Å 2 )), is the use of mono-and divalent cations, which form distinguishable adduct complexes with the target analytes, and has led to successful separations of isomeric carbohydrates, lipids, and peptides [8][9][10][11][12][13]. The improved resolution was due to mobility shifts in one of the isomeric forms as a result of conformational changes induced by cation adduct formation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, for other classes of molecules, separation of isomers, including chiral discrimination, has been previously demonstrated [39,40]. Recent studies of complex lipids using conventional drift tube ion-mobility indicate that mobility is most strongly correlated with mass and thus tends to separate lipids based on class rather than isomeric variations [40,41]. Shvartsburg et al have shown, however, that differential ion-mobility is capable of resolving sn-positional isomers in diacylglycerols, which augurs well for the future discrimination of other types of lipid isomers [42].…”
Section: Double Bond Stereochemistrymentioning
confidence: 99%
“…Both approaches are capable of identifying dozens-hundreds of lipids in a reliable manner, although they may yield additional complementary data when carried out simultaneously on the same sample. Ion mobility MS is being actively pursued in order to enhance lipidomic analyses as well, but with limited success so far [61][62][63]. …”
Section: Ms Analysis Of Lipidsmentioning
confidence: 99%
“…TWIMS has been studied in lipidomic applications as well, but in a more general manner. General applicability of IM-MS for distinguishing phospholipid classes has been investigated by Jackson et al [63]. Similarly, unsaturated phosphatidylcholines have been investigated by Kim et al [61].…”
Section: Ms Separations In the Gas Phasementioning
confidence: 99%